KAJIAN NORMATIF TENTANG DEWAN PERWAKILAN RAKYAT DALAM SISTEM KETATANEGARAAN INDONESIA - Miswar, Miswar; Firmanto, Fakhry (Pahlawan Tuanku Tambusai University, 2025)
The House of Representatives (DPR) is a legislative body that plays a central role in the Indonesian state system. Its position is affirmed in the 1945 Constitution of the Republic of Indonesia (UUD 1945) as the institution that holds the power to form laws. This study aims to normatively examine the position, functions, rights, and obligations of the DPR, as well as the problems that arise in the implementation of its legislative, oversight, and budgetary functions. The research method used is normative legal research with a statutory and conceptual approach. The results of the study indicate that although the DPR has a strong normative role, in practice there are still weaknesses in the effectiveness of the implementation of its oversight and legislative functions, which are often influenced by the dynamics of practical politics. Keywords : DPR, legislative function, state system, normative studies